Correlation between PMT and CPT after dynamic compaction in reclaimed calcareous sand - Hamidi, B.; Nikraz, Hamid; Varaksin, S. (Australian Geomechanics Journal, 2015)
Regardless of the reclamation technique that is used, sand reclamations are placed in a loose state, and are potentially subject to settlement under self-weight, insufficient bearing capacity and excessive settlements under loads. Dynamic compaction has proven to be a suitable ground improvement technique for the treatment of reclaimed sands, whether with silica or carbonate mineralogy. The pressuremeter test (PMT) has been systematically used in many dynamic compaction projects, but occasionally other tests such as the Cone Penetration Test (CPT) are used for quality control and verification purposes, and it would advantageous to be able to compare the results of the CPT with previously published projects that have used the PMT. While there are publications that have correlated CPT to PMT, the authors are not aware of any such publications for calcareous sands. In this paper, after a brief review of dynamic compaction, previous PMT and CPT correlations will be presented, and two projects in Qatar and UAE in which reclamation was done by hydraulic filling of calcareous sand will be discussed. The loose fills were improved by dynamic compaction, and CPTs and PMTs were carried out for testing purposes. This study suggests that PMT-CPT correlations derived in the two projects are in the same order, and do not appear to be dependent on depth. A relationship is proposed for estimating the elasticity modulus of improved calcareous sand using CPT cone resistance.